ONLINE GAMING, TRANSFORMATIONAL LEADERSHIP, AND EMPLOYEE PERFORMANCE AMONG MILLENNIALS AND GENERATION Z - Zera Fitrizon; Adriani, Zulfina; Lubis, Tona Aurora (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This study examines the effects of Online Game Usage and Transformational Leadership on Employee Performance and investigates the moderating role of Transformational Leadership. The research involved Millennial and Generation Z employees at PT PLN (Persero) UP3 Jambi. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The findings show that Online Game Usage has a positive and significant effect on Employee Performance, indicating that controlled gaming undertaken at appropriate times may coexist with effective work performance. Transformational Leadership also has a positive and significant effect on Employee Performance by strengthening employee motivation, encouraging new ideas, and supporting individual development. However, Transformational Leadership does not significantly moderate the relationship between Online Game Usage and Employee Performance. This indicates that leadership contributes directly to performance, whereas the consequences of online gaming are primarily determined by employees’ timing, motivation, and personal control. The study highlights the importance of strengthening transformational leadership practices while encouraging responsible digital behavior among employees. Keywords: Online Game Usage, Transformational Leadership, Employee Performance, Millennials, Generation Z